The Role of Learning Agility in Performance Improvement - Hidayat, Zainul; Yatminiwati, Mimin; Ermawati, Emmy (International Journal of Accounting and Management Research, 2025)
Using a Systematic Literature Review (SLR) methodology, this study attempts to investigate how Learning Agility might enhance both individual and organisational performance.. Learning Agility is defined as the ability to learn from experience and apply that learning to new situations. This research reviews related literature from various sources to identify the main dimensions of Learning Agility and its relationship with performance improvement, both at the individual and organizational levels. The results show that Learning Agility contributes significantly to performance improvement. The findings also underline the importance of developing Learning Agility with various programs within the organization.